PENGARUH RETURN ON EQUITY (ROE) DAN QUICK RATIO (QR) TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SUB SEKTOR MAKANAN & MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Eliza, Apria; Mikial, Mikial; Mayasari, Rosalina Pebrica (Forum Bisnis Kewirausahaan, 2024)
Abstract: This research aims to determine and prove the effect of Return On Equity (ROE) and Quick Ratio (QR) on company Value with Dividend policy as an intervening variable, both directly and indirectly. The population in this research is food and beverage sub-sector companies listed on the IDX for the 2018-2022 period. The sampling in this research was carried out using a purposive sampling method, namely determining the sample based on certain consideRations. Based on predetermined criteria, 12 companies were obtained as samples for this research with an observation period of 5 years. The data analysis technique used in this research is a quantitative analysis technique with multiple linear regression tests and Sobel tests using the eviews program. The results of this research show that (1) the Return On Equity (ROE) variable influences Dividend Policy (2) The Quick Ratio (QR) variable influences Dividend Policy. (3) The Return On Equity (ROE) variable influences company Value. (4) The Quick Ratio (QR) variable influences company Value. (5) Dividend Policy Variables influence Company Value. (6) The Return On Equity (ROE) variable influences company Value through Dividend policy. (7) The Quick Ratio (QR) variable influences company Value through Dividend policy. The results of the coefficient of determination test (R2 test) obtained an R-squared Value of 0.84907 or 84.90%. Keywords: Return On Equity (ROE), Quick Ratio (QR), Dividend Policy, Company Value